Powikłania okresu okołooperacyjnego z uwzględnieniem ich patogenezy u pacjentów chorych na cukrzycę - Joanna Świrska (Menopause Review, 2011)
Diabetes is a common and growing problem in the world. It is regarded now by World Health Organizationas the first non-contagious epidemic. At present there are over 285 million people in the world affected by thisdisease and this number is estimated to reach, in the year 2030, the value of 438 million. In the European Unionthis disease concerns at the moment over 30 million people, whereas in Poland there are over 2 million peoplewith diabetes which accounts for 5% of Polish population. Diabetic patients admitted to hospital constitutefrom 10 to 25% of all hospitalized patients, however, these data are underestimated as they do not includepatients with undiagnosed diabetes. Patients with diabetes are at a higher risk of perioperative complications.The course and prognosis of the perioperative period in this group of patients depends on many factors. Beingaware of them and providing proper perioperative management results in the reduction of complications tothe values typical of normoglycemic population. Furthermore, the right perioperative management reduces thehospitalization costs of diabetic patients.This study, focused on diabetic patients, including those undergoing gynecological surgery, has set itselfthe following aims: to review and explain the pathogenesis of the most common perioperative problems andindicate ways of preventing them.